Knowledge and Practice on Menstrual Hygiene among Reproductive Age Groups in Birendranagar Municipality, Surkhet, Nepal - Acharya, Samikshya; Malla, Nabina (One Health Journal of Nepal, 2021)
Introduction: Reproductive aged group is usually defined as 15-49 years. There are many regions in Nepal where women of childbearing age are uneducated and unaware of how to manage menstrual hygiene. The main aim of this study was to identify the level of knowledge and practice of menstrual hygiene among Reproductive Age Grouped Women of Birendranagar Municipality-.8, Karnali Province. Methods: A descriptive cross-sectional study design was done among 373 reproductive aged women of ward no. 8, Birendranagar Municipality, after taking ethical approval. Participants were recruited through systematic random sampling. Data was collected by using a semi-structured questionnaire via face-to-face interviews. All the extracted data were entered and analysed using SPSS version 20, where descriptive analysis was done and presented using frequency and percentage. Results: In overall, 88.7% were found properly practising menstrual hygiene with great access to toilet(100%) and water facility(99.5%). Only half (48.3%) of the respondents were found to have adequate knowledge on menstrual hygiene where most of the respondents were taught about menstruation by their mother(42.1%). Conclusions: Despite the good level of practice of menstrual hygiene, the knowledge of menstrual hygiene was still lacking. This indicates the need of awareness on menstrual hygiene practice.